Using soccer games as an instrument to forecast the spread of COVID-19 in Europe - Gomez, J.-P.; Mironov, M. (SSRN, 2020)
We provide strong empirical support for the contribution of soccer matches held in Europe during the first quarter of 2020 to the spread of the COVID-19 virus. We analyze more than 1,000 games across 194 regions from 10 European countries. Daily cases of COVID-19 grow significantly faster in regions where at least one soccer game took place two weeks earlier, consistent with the existence of an incubation period and the lack or massive testing in the early phases of the pandemic. Game attendance and venue capacity show an analogous pattern. These results weaken as we include stadiums with smaller capacity, consistent with a minimum agglomeration needed for the virus transmission to be detectible. We discuss the relevance of these variables as instruments for the identification of the causal effect of COVID-19 on firms, the economy, and financial markets.